Investigation of Subgrade Particles Acceleration Due To Dynamic Loading - Rini Kusumawardani (Graduate Program of Syiah Kuala University, 2017)
Detail investigation on flexible pavement due to of vehicles traversed was presented in this paper. The behaviour of subgrade particles acceleration on flexible pavement are investigated and is explained in order to obtain the comprehensive understanding about pavement. Investigation were conducted in the highway which have a yearly higway construction problems. The data collected represented three axis main principal direction (x, y and z axis) movements. The main objectives of this work is to evaluating the effects of vehicle traverse on the pavement to several parameter, such as acceleration, thickness of pavement and natural frequency of subgrade. The results are useful as a new approach of pavement design as well as flexible or concrete pavement by considering some parameters analyzed.